Concussion in ice hockey--A cohort study across 29 seasons - Pauelsen, M.; Nyberg, G.; Tegner, C.; Tegner, Y. (Clinical Journal of Sport Medicine, 2017)
OBJECTIVE: The aim of this study was to analyze the concussion incidence rate ratios across 29 seasons in a Swedish Hockey League team. DESIGN: Cohort study over 29 seasons within one Swedish elite series ice hockey team. PARTICIPANTS: All players who were part of one Swedish elite ice hockey team during the research period gave consent for participation in the study. INDEPENDENT VARIABLES: Exposure to top-level Swedish ice hockey. MAIN OUTCOME MEASURES: Incidence rate ratio for concussion and rehabilitation periods due to concussion were calculated and analyzed. RESULTS: During the research period, 267 players in total were part of the team. A total of 1638 traumatic injuries were registered, of which 162 were concussions. Incidence rates (IRs) ranged from 0/1000 games during the first season to 118/1000 games for the final recorded season. The incidence rate ratio was 1.06 (confidence interval, 1.03-1.10) for the entire research period. A shift toward longer rehabilitation periods was discovered. CONCLUSIONS: This study showed a significant increase of concussion IR and a trend toward longer rehabilitation periods due to concussion. Possible risk factors were discussed. Risk behavior and rehabilitation protocols should be prioritized areas in the research of concussion in ice hockey. ABSTRACT FROM AUTHOR